Self-Efficacy, Proactive Personality, and Social Support as Predictors of Entrepreneurial Intention among Management Students - Krisnova Nastasia; Ria Okfrima (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2026)
Entrepreneurship has become one of the primary strategies for promoting economic growth, reducing graduate unemployment, and fostering innovation in developing countries. Nevertheless, many university graduates continue to prefer salaried employment over entrepreneurial careers. Entrepreneurial intention has been widely recognized as the most reliable predictor of entrepreneurial behavior, yet empirical evidence concerning the combined influence of psychological and social determinants among Indonesian university students remains limited. This study aimed to examine the effects of self-efficacy, proactive personality, and social support on entrepreneurial intention among management students enrolled at private universities in Padang City. A quantitative cross-sectional survey design was employed involving 219 respondents selected using cluster sampling techniques. Data were collected through standardized Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 23 after satisfying classical assumption tests. The findings indicate that self-efficacy, proactive personality, and social support positively and significantly influence entrepreneurial intention both individually and simultaneously. The regression model explains 34.4% of the variance in entrepreneurial intention. Self-efficacy emerged as the strongest predictor, followed by social support and proactive personality. These findings emphasize the importance of strengthening students' entrepreneurial confidence, proactive characteristics, and supportive social environments through entrepreneurship education. This study contributes empirical evidence supporting the integration of psychological and social dimensions into entrepreneurship development programs within higher education institutions.